2015
DOI: 10.1016/j.compbiomed.2015.01.010
|View full text |Cite
|
Sign up to set email alerts
|

BtoxDB: A comprehensive database of protein structural data on toxin–antitoxin systems

Abstract: The compilation of all protein structural data on TA systems in one platform is highly useful for researchers interested in this content. BtoxDB is publicly available at http://www.gurupi.uft.edu.br/btoxdb.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…The cognate toxin and antitoxin of a TA system are small proteins encoded by two genes organized in one operon (36). The activity of the toxin can be neutralized by forming a protein complex with its cognate antitoxin (30,37).…”
Section: Discussionmentioning
confidence: 99%
“…The cognate toxin and antitoxin of a TA system are small proteins encoded by two genes organized in one operon (36). The activity of the toxin can be neutralized by forming a protein complex with its cognate antitoxin (30,37).…”
Section: Discussionmentioning
confidence: 99%
“… Antitoxin grouping is based on Leplae et al [ 119 ] and consistent with that found by Arbing et al [ 120 ]. ¥ Toxin Antitoxin Database [ 101 ]; ▯ Number of entries in the Protein Families Database [ 121 ]; ❖ Database of toxin-antitoxin structural depositions database [ 122 ]; § Alignments were constructed using the ClustalW algorithm, and were visualized as a consensus sequence with the online server WebLogo [ 123 ] and with CLC Genomics Workbench© 8.0.3 [ 124 ]. N.D. , no data available.…”
Section: Figurementioning
confidence: 99%
“…The product of the antitoxin gene, which can be either RNA or protein, is usually less stable compared to the toxin protein. Depending on the mechanism by which the antitoxin neutralizes the toxin, TAs have been categorized into six different types: (i) Type I, in which the antitoxin mRNA binds to its complementary toxin mRNA to prevent translation of the toxin gene; (ii) Type II, the antitoxin is a protein that forms a stable complex with the toxin protein and blocking the active site of the toxin under normal growth conditions; (iii) Type III, the antitoxin is an RNA with multiple tandem repeats that binds directly to the toxin protein rendering the toxin inactive; (iv) Type IV, the antitoxin protein does not bind to the toxin, but antagonize the toxin effect by competing for binding to the cellular target; and (v) Type V, the antitoxin protein is an RNase that cleaves directly its cognate toxin mRNA (Alonso et al, 2007 ; Hayes and Van Melderen, 2011 ; Masuda et al, 2012 ; Cataudella et al, 2013 ; Unterholzner et al, 2013 ; Barbosa et al, 2015 ). A likely new type of TA system (a possible type VI) was recently discovered in Caulobater crescentus where both the SocA antitoxin and SocB toxin are proteins, as in types II and IV TA systems.…”
Section: Introductionmentioning
confidence: 99%